Good Governance as a Tool of Sustainable Development - Stojanović, Ilija; Ateljević, Jovo; Stević, R. Stevan (European Journal of Sustainable Development, 2016)
Growing concern about environmental degradation, disappointment with development efforts to reduce poverty and inequality on a global scale together with economic and socio-political instability has shifted focus from the model of economic growth to the new model of sustainable development. Despite the new orientation of development economics, the question on how to achieve sustainable development goals still remains. In order to avoid failure of the neoliberal agenda, the revised version of Washington Consensus focusing on good governance has taken the leading role in development policy. The aim of this research is to test the links between a fuzzy concept of good governance and very heterogonous dimensions of sustainable development. Our research aims to analyze the effects of good governance on particular indicators of sustainable development, especially of socio-economic development, at the level of different categories of countries. This study reveals that statistical significance, direction and intensity of the effects of good governance dimensions vary in relation to the selected indicator of sustainable development and affiliation to the particular category of countries. These results suggest that there is no “one size fits all” model of good governance promoted as a universal mantra of sustainable development putting into question the principles of post-Washington consensus as the key response to modern developmental challenges. Keywords: good governance, sustainable development